Maladaptive reactions of internship doctors during the period of adaptation to professional activities - Valeriy V. Vyun; Anna M. Kozhina (Kazimierz Wielki University, 2017)
During the work on the basis of a systematic approach to the study of mechanisms of psychological adaptation of the internship doctors to the profession has developed a system of medical and psychological support during the specialist professional training. It was found that in the period of adaptation to professional activity by internship doctors marked asthenic, hypersthenic, apathetic, depressed, addictive and psychosomatic options of maladaptive reactions. Developed and tested system of medical and psychological support to the doctor in the period of adaptation to professional activity, which includes: a program of psychological and psychosocial training, system of psychological counseling for internship doctors. The results of the 3-year follow-up monitoring indicate a high efficiency of the proposed system of medical and psychological support to the doctor in the period of adaptation to the professional activity.